Review South Sulawesi Human Development Index Using Methodology New - Iwan Harsono; Syamsu Rijal; Andi Zakinah Juniarti; Samsuardi Said; Rezki Fitriani (Universitas Muhammadiyah Palu, 2024)
This study for review returns How quality source Power man especially in South Sulawesi Province using perspective number new where measurements Human Development Index according to UNDP reviewed with track and analyze Health and Education expenditure data using panel data, namely cross-sections and time series for see influence in a way statistics. The results obtained writer that is Health shopping has influence negative and not significant to Human Development Index, Education Expenditure has influence negative and not significant to Human Development Index in South Sulawesi Province. Attention to variables social need improved, okay from facet utility budget and whether distribution of Education and Health funds already appropriate target or No